Cytoskeletal Dynamics: Concepts in Measles Virus Replication and Immunomodulation - Avota, Elita (Molecular Diversity Preservation International (MDPI), 2011)
In common with most viruses, measles virus (MV) relies on the integrity of the cytoskeleton of its host cells both with regard to efficient replication in these cells, but also retention of their motility which favors viral dissemination. It is, however, the surface interaction of the viral glycoprotein (gp) complex with receptors present on lymphocytes and dendritic cells (DCs), that signals effective initiation of host cell cytoskeletal dynamics. For DCs, these may act to regulate processes as diverse as viral uptake and sorting, but also the ability of these cells to successfully establish and maintain functional immune synapses (IS) with T cells. In T cells, MV signaling causes actin cytoskeletal paralysis associated with a loss of polarization, adhesion and motility, which has been linked to activation of sphingomyelinases and subsequent accumulation of membrane ceramides. MV modulation of both DC and T cell cytoskeletal dynamics may be important for the understanding of MV immunosuppression at the cellular level.